Disruptive Business Model Innovation: How a Tech Firm is Changing the Traditional Taxi Service Industry - Bashir, Makhmoor; Yousaf, Anish; Verma, Rajesh (Indian Journal of Marketing, 2016)
Speaking at the IOD Annual Convention 2014 in London, Travis Kalanick, CEO of Uber made a bold statement that "Uber is not a taxi service provider." This statement took everybody by surprise as Uber has become one of the biggest taxi service providers, having global presence in more than 55 countries and 200 plus cities worldwide. Uber has emerged as a biggest start-up in corporate America since the last 5 years, and is expected to overtake some of the biggest companies in United States in a couple of years down the line. The company was expected to touch $10 billion in revenues by the end of 2015, while a company like Facebook, after completing 10 years of its operations for the first time, is expected to earn $10billion in revenues this year. The case highlighted how Uber has transformed a traditional capital intensive industry into a high-tech business. The company relies on an independent pool of contractors (cab owners/drivers) who register themselves on Uber's website and for every ride, 80% of the payment goes to the driver, and Uber takes the rest 20%. The case further illustrated the various challenges which the company is facing in its global expansion, particularly in countries like Spain and India, and questioned the validity of surge pricing.